2015
DOI: 10.1080/02701367.2015.1053105
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Influences on Preschoolers' Physical Activity Levels in Various Early-Learning Facilities

Abstract: This research underscores the need to encourage/support preschoolers' active behaviors in early-learning settings, particularly for those in center- and home-based childcare. Furthermore, this article highlights environmental and staff characteristics on which future PA programming should focus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
49
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 30 publications
5
49
1
1
Order By: Relevance
“…Additionally, contextual information regarding the types of sedentary activities toddlers engage in would help with the interpretation of sedentary time estimates, as some sedentary behaviours offer more educational value than others. Moreover, it would be beneficial to explore the childcare environment as a platform for intervention within this population, as childcare centre characteristics have consistently been associated with physical activity rates in preschoolers [73]. Education and promotion of the 24-h movement guidelines among parents, guardians, pediatricians, and early childhood educators may benefit young children in developing and maintaining healthy movement profiles.…”
Section: Future Research Efforts and Directionsmentioning
confidence: 99%
“…Additionally, contextual information regarding the types of sedentary activities toddlers engage in would help with the interpretation of sedentary time estimates, as some sedentary behaviours offer more educational value than others. Moreover, it would be beneficial to explore the childcare environment as a platform for intervention within this population, as childcare centre characteristics have consistently been associated with physical activity rates in preschoolers [73]. Education and promotion of the 24-h movement guidelines among parents, guardians, pediatricians, and early childhood educators may benefit young children in developing and maintaining healthy movement profiles.…”
Section: Future Research Efforts and Directionsmentioning
confidence: 99%
“…Accordingly, early childhood is a critical time to implement health promotion programs that promote physical activity and limit sedentary behaviours, as early prevention appears to be the most cost‐effective and efficacious strategy against childhood obesity and a range of other adverse health conditions 8,16–18 . Previous research has established several modifiable factors in preschool environments that significantly increase physical activity and lessen sedentary time for children while in care: high service quality; 19 written physical activity policies; 20 equipment variety and portability; 19,21,22 larger playgrounds 19,23 and indoor play space; 23,24 time spent outdoors; 24,25 regular teacher‐led structured activity; 20 low electronic media use 19,26 and teacher training in physical activity 4,19 …”
mentioning
confidence: 99%
“…The results indicated that Flemish children who started attending school at the age of 2 years 6 months, and who participated in a more formal curriculum, performed significantly better in the Movement Assessment Battery for Children than the standardized sample (attending preschool classes at the age of 5y). The level of childhood physical activity was also affected by the environment of preschool they attended when the children's age, sex, or other environmental conditions were considered . Recently, an intervention study reported that school environment affected children's physical level when adjusting for sex, age, and body mass index centiles .…”
mentioning
confidence: 99%
“…The level of childhood physical activity was also affected by the environment of preschool they attended when the children's age, sex, or other environmental conditions were considered. 11,12 Recently, an intervention study reported that school environment affected children's physical level when adjusting for sex, age, and body mass index centiles. 13 Children attending childcare centres have also been shown to have less developed fine motor skills than those in private schools.…”
mentioning
confidence: 99%